Assessment of industrial nitriding processes for fusion steel applications. (December 2017) - Seitz, M.; Hoffmann, J.; Rieth, M.; Margraf, P.; Senn, R.; Klimenkov, M.; Lindau, R.; Baumgärtner, S.; Jäntsch, U.; Franke, P.; Möslang, A.
Highlights: The effect of an industrial scale nitriding process on the mechanical behaviour of RAFM steels is studied. The fatigue lifetime is prolonged for the nitrided EUROFER97 in comparison to standard treatments. Only minor increase of the DBTT was observed after the treatments. The fatigue properties of ODS-EUROFER were studied. Microstructural changes in the boundary layer after nitriding was studied by FIB and TEM. Abstract: The 9Cr steels EUROFER and F82H-mod are the candidate materials for future fusion reactors. The extension of the operation limits including temperature, strength and toughness are still the scope of ongoing research. In a pulsed reactor operation, fatigue lifetime is one of the major properties for the steels. While the oxide dispersion strengthened EUROFER-ODS variant showed significant improvements in this area, the production costs and availability of large quantities of materials drastically limits its applications. In the present study, different surface nitriding treatments of EUROFER972 have been performed and the impact on microstructure, dynamic fracture toughness and high temperature fatigue has been analysed. Four different states of EUROFER including different heat treatments, nitriding of the surface and the ODS variant are tested and compared in this work. Low cycle fatigue tests show the improvements after certain treatments. Charpy impact tests and microstructural investigation by scanning electron microscopy and analytical transmission electron microscopy are also performed to compare the materials against the reference (EUROFER97). While conventional gas nitriding showed no beneficial effect on the material, the Hard-Inox-P treatment showed a significant improvement in the cycles to failure while retaining an acceptable toughness. Microstructural investigations showed the presence of very small chromium- and nitrogen-rich precipitates in the area close to the surface.